Multifunctional Metallic Hollow Sphere Structures Manufacturing, Properties and Application - Augustin, Christian (Engineering Materials,, 2009)
Multifunctional Metallic Hollow Sphere Structures are an emerging new material category, belonging like metal foams to the class cellular metals. Thanks to their advantageous mechanical and sound absorbing properties, Multifunctional Metallic Hollow Sphere Structures are very promising for various applications and our technological knowledge makes them ready for industrial usage. This reference gives a complete overview on this new materials class, the fundamentals, the applications and the perspective for future use. It provides the foundations for a profound understanding (production and processing), their physical properties (surface properties and stalility) and applicaltion (in particular for sound absorption and chemical adsorption in structural parts). The book is written for material scientists, product designers and developers as well as academic researches and scientists.